Bacteremic Leptospirosis to Severe Leptospirosis: A Case Series - Surontee, Rayeed Anan; Hoque, Mohammad Mahfuzul; Rashed, Md Rajilur; Buswas, Subrata Kumar; Reegbi, Nurunnahar; Bari, Md Shafiqul (Bangladesh Journal of Medicine, 2026)
Leptospirosis is a common zoonotic infection in tropical countries due to contact with water contaminated by the spirochaete Leptospira. Here, we present four different and unrelated cases of patients presenting with leptospirosis. A23-year-old pregnant woman hailing from Savar presented with aseptic meningitis due to leptospirosis after bathing in contaminated water.She did not respond to Ceftriaxone initially and was treated with adjunct Dexamethasone according to the treatment protocol for bacterial meningitis. We also present cases of three middle-aged gentlemen presenting with Weil’s disease. Out of these three patients, two of them presented with fever and jaundice, and one presented with fever, jaundice, and acute kidney injury. Clinical vigilance is required to ensure appropriate recognition of patients with leptospirosis, as the presentation is variable. Bangladesh J Medicine 2026; 37(2): 165-171